Development of cumulative rainfall threshold for landslide occurrence in peninsular Malaysia - Ali, Supiah; Kasim, Norhidayu; Saiful Anuar, Afiq Aiman; Ruslan, Muhammad Imran; Wan Azahar, Wan Nur Aifa; Ramli, Ahmad Bukhari (Malaysia Institute of Planners, 2023)
Significant issues related to landslides are exposed tremendously in Peninsular Malaysia which have an impact on human beings, animals as well as properties. Reported over twenty-eight significant landslides taking place between 1993 and 2011 which resulted in more than 100 deaths in total. Most of the landslides are the consequences of accumulation of water in underground soil which is connected to rainfall threshold. To establish an empirical Cumulative-Duration threshold through linear regression, analysis of 69 landslide incidents undertaken as well as rainfall data sourced from Public Works Department (PWD) and Department of Irrigation and Drainage (DID) were collected. A comprehensive assessment of all gathered parameters conducted to achieve the confidential purpose of this research which is to determine the threshold for cumulative rainfall event duration which can be utilized in early warning systems and planning for future safety measures. Thus, correlation between rainfall patterns and landslide events are observed. Cumulative rainfall threshold produced an equation E = with identical range of event duration 1 < D < 2448 h which acts as a critical line of landslide occurrences. Validation of threshold was revised using recent landslide cases to acquire new threshold values to represent current rainfall induced landslides. The threshold serves as an early warning mechanism and planning to protect lives and property